2008
DOI: 10.2164/jandrol.107.003392
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Juvenile Rats to the Phytoestrogen Daidzein Impairs Erectile Function in a Dose‐Related Manner in Adulthood

Abstract: Health benefits of isoflavones such as genistein and daidzein have led to an increasing interest in consuming soybeans or soy-containing food. However, possible adverse effects of such plant estrogens on the male reproductive system, particularly penile erection, have not been sufficiently evaluated. In previous research, we observed that exposure of adult rats to daidzein could attenuate apomorphine-induced erections. To identify the impact of daidzein exposure in early life on erectile function, we evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 31 publications
1
29
1
4
Order By: Relevance
“…The results showed that daidzein enhanced hCGstimulated steroidogenesis of 3-day-old mouse Leydig cells at concentration of up to 10 -4 M. This is contradictory to many in vivo experiments showing that isoflavones, including daidzein, decrease testosterone concentration [6,7,9]. It has been reported that isoflavone, including daidzein can exert inhibitory feedback on the hypothalamus-pituitarygonadal axis [21].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The results showed that daidzein enhanced hCGstimulated steroidogenesis of 3-day-old mouse Leydig cells at concentration of up to 10 -4 M. This is contradictory to many in vivo experiments showing that isoflavones, including daidzein, decrease testosterone concentration [6,7,9]. It has been reported that isoflavone, including daidzein can exert inhibitory feedback on the hypothalamus-pituitarygonadal axis [21].…”
Section: Discussionmentioning
confidence: 66%
“…For example, exposure of juvenile rats to daidzein in relatively large amounts could impair erectile function and decrease plasma testosterone levels in adulthood [6]. Soy formula milk could decrease marmoset monkey blood testosterone levels [7].…”
Section: Brief Communication (Original)mentioning
confidence: 99%
“…The presence of the soy phytoestrogens, can lead structural and functional modifications in the reproductive tract during development and adulthood (Cardozo & Baó, 2007;Cederroth et al, 2010). In concurrence with a report by Pan et al (2008), consumption of large amounts of soy phytoestrogens can trigger erectile dysfunction, which involves erectile tissue. Huang et al (2008) observed the morphological action of daidzein in 90-day-old rat penis.…”
Section: Introductionmentioning
confidence: 86%
“…Relatively large amounts cause histological changes in the penile structure of rats, including an increase in collagen and a reduction in smooth muscle and elastic fiber content [34]. When juvenile rats were exposed to daidzein, erectile function was impaired when the rats matured into adults in a dose-dependent manner [35]. Apart from animal models, there has been a case report of an 18-year-old who developed hypogonadal ED due to a high soy vegan diet that was reversible with diet cessation [36].…”
Section: Etiology Of Erectile Dysfunctionmentioning
confidence: 99%